Treatment of Fractures of the Tibial Diaphysis Using External Fixator Compared with Locked Intramedullary Nails() - Cardozo, Rodrigo Tavares (Rev Bras Ortop, 2013)
OBJECTIVE: To compare efficiency of external fixator in modular form with unilateral and uniplanar intramedullary locked seeking definitive treatment of fractures of the tibia diaphysis. METHODS: Orthopedic surgical treatments were compared to 50 patients with definite diafisaria fracture of the tibia, through the use of the external fixator, modular and intramedullary locked. The fractures were treated at emergency hospital school of External fixators Orthopedics and Traumatology service in the period from January 2007 to January 2011, Locked Intramedullary Nail with a variation of 15 to 48 weeks. RESULTS: this study has proven functional results and Tibial fractures/therapy excellent consolidation when locked intramedullary rods were used and the versatility and speed of application of external fixator reaching the necessary stabilization of bony fragments. Consolidation of fractures was obtained in 95 cases when using the intramedullary locked and 90 cases undergoing external fixation. CONCLUSIONS: the definitive treatment of tibial diaphysis fractures by external fixator modular presented themselves as valid alternative treatment in patients who could not be submitted for early conversion to internal osteosynthesis or when the intramedullary nails are not available to the surgeon.